2021
DOI: 10.3390/math9050532
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology for Winning Consumer Loyalty: Social Norm Analysis Using Structural Equation Modeling

Abstract: Remarkable changes have taken in social operation mode and consumers’ behavior mode because of the foot ban during the pandemic spread of COVID-19. Digital technologies such as Blockchain have shown potential in gaining competitive advantages for enterprises in such situations. This study aims to provide an insight into how to gain consumer loyalty through the use of modern and efficient Blockchain technology. In contrast to the current literature, this study combined the technology acceptance model of planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 111 publications
1
21
0
Order By: Relevance
“…Research findings supported previous research by those who found that SOCN has a major influence on dwellers' intentions. Another study by [130] found that dwellers' behavior is directly affected by social norms. According to [131], the result of a consumer's product intake is predetermined by social norms.…”
Section: Social Norms and Willingness To Adopt Solar Pvmentioning
confidence: 99%
“…Research findings supported previous research by those who found that SOCN has a major influence on dwellers' intentions. Another study by [130] found that dwellers' behavior is directly affected by social norms. According to [131], the result of a consumer's product intake is predetermined by social norms.…”
Section: Social Norms and Willingness To Adopt Solar Pvmentioning
confidence: 99%
“…The advent of this system was a pivotal event in the history of cryptocurrencies. In 2008, Satoshi Nakamoto, a Japanese individual who might not be real wrote a paper called 'Bitcoin: A peer to peer electronic cash system' based on Bitcoin (Pérez-Sánchez et al, 2021, Willie, 2019. Nakamoto is widely regarded as the developer of this revolutionary blockchain technology who improved the design by adding blocks with the original chain and eliminating the need for third parties' involvement (Pérez-Sánchez et al, 2021).…”
Section: History Of Blockchainmentioning
confidence: 99%
“…In 2008, Satoshi Nakamoto, a Japanese individual who might not be real wrote a paper called 'Bitcoin: A peer to peer electronic cash system' based on Bitcoin (Pérez-Sánchez et al, 2021, Willie, 2019. Nakamoto is widely regarded as the developer of this revolutionary blockchain technology who improved the design by adding blocks with the original chain and eliminating the need for third parties' involvement (Pérez-Sánchez et al, 2021). The new improvements in the technology became capable of containing secured data and reducing the risk of counterfeiting data history (Valeri & Baggio, 2020).…”
Section: History Of Blockchainmentioning
confidence: 99%
“…This approach proposes that to manage such a process successfully, the entrepreneur must possess a specific profile (Schumpeter, 1934;Lupiáñez et al, 2014;Suárez-Álvarez & Pedrosa, 2016). Among the entrepreneurial traits that most stand out in the literature are psychological traits, motivations, experiences, skills, and behaviours (Timmons, 1999;Pérez-Sánchez et al, 2021). However, at present, the focus on competencies and vocation predominates in the study of entrepreneurship, aspects on which more research is needed (Wagener et al, 2010;Kuratko, 2014).…”
Section: Introductionmentioning
confidence: 99%